2022
DOI: 10.1200/po.21.00002
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Molecular Biomarkers Predictive of Resistance to CDK4/6 Inhibition in Metastatic Breast Cancer

Abstract: Cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors have revolutionized the treatment of hormone-positive metastatic breast cancers (mBCs). They are currently established as standard therapies in combination with endocrine therapy as first- and second-line systemic treatment options for both endocrine-sensitive and endocrine-resistant mBC populations. In the first-line metastatic setting, the median progression-free survival for the three currently approved CDK4/6 inhibitors, palbociclib, ribociclib, and abema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 60 publications
2
38
0
Order By: Relevance
“…Despite this indisputable success, the knowledge of resistance mechanisms and the identification of potential biomarkers still represent an unmet clinical need. To this aim, several retrospective and prospective biomarker studies have been conducted [ 20 ]. Exploratory analyses of PALOMA-2 and 3 and MONALEESA trials have suggested a possible correlation between intrinsic subtypes and survival outcomes of MBC patients treated with CDK4/6i in addition to ET [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this indisputable success, the knowledge of resistance mechanisms and the identification of potential biomarkers still represent an unmet clinical need. To this aim, several retrospective and prospective biomarker studies have been conducted [ 20 ]. Exploratory analyses of PALOMA-2 and 3 and MONALEESA trials have suggested a possible correlation between intrinsic subtypes and survival outcomes of MBC patients treated with CDK4/6i in addition to ET [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous genomic alterations affecting cell cycle-related genes have been demonstrated to induce acquired resistance to CDK4/6i in patients and preclinical models. These alterations include loss of RB1 and FAT1; down-regulation of the intrinsic CDK4/6 repressors p27 and p21; activating mutations in the phosphatidylinositol 3-kinase (PI3K) signaling pathway; amplification of CDK6, CCNE1, FGFR1, and AURKA; and up-regulation of cyclin D1, cyclin D2, CDK2, MYC, PDK1, and SKP2, among others (4,(13)(14)(15)(16)(17)(18)(19). The diversity of mechanisms that have been associated with CDK4/6i resistance has complicated the understanding of this disease entity, as well as the development of second-line therapeutic strategies to effectively address it.…”
Section: Introductionmentioning
confidence: 99%
“…Since our ultimate goal is to delay or prevent the onset of drug resistance, adding resistance mechanisms to the model is a critical requirement for future work (Wander et al, 2020; Asghar et al, 2022; Pandey et al, 2022, Papadimitriou et al, 2022). The cyclinD1 change mentioned above is a minor step in that direction, but the development of resistance is a complex, multi-faceted process and there are many different pathways that lead to a drug resistant state (Lloyd et al, 2022; Watt et al, 2022).…”
Section: Discussionmentioning
confidence: 99%